Análisis organizacional del Partido de la Democracia Social Brasileña en el Estado de San Pablo (1988-2006) - Kerbauy, María Teresa Miceli [UNESP]; Assumpção, Raiane (My University, 2012)
The article represents a theoretical and methodological approach to the analysis of organizational dynamics of political parties today, based on a study of the Party of Brazilian Social Democracy (PSDB) in the State of Sao Pãulo (period between 1988 to 2006). It is hypothesized that the structure and the institutional rules of a particular party, or even their election results, are insufficient to explain the inner workings, such as the role of party organization in the electoral system. An approach that articulates the relationship patterns, election results and posts held in the party, identified the factors that explain the political capital that circulated within the party and ensured its organizational dynamics over the period analyzed.

El artículo representa un enfoque teórico-metodológico para el análisis de la dinámica organizacional de los partidos políticos en la actualidad, a partir de una investigación realizada sobre el Partido de la Democracia Social Brasileña (PSDB) en el estado de San Pablo (periodo entre 1988 hasta 2006). Se partió de la hipótesis de que la estructura y las normas institucionales de determinado partido, o incluso sus resultados electorales, son insuficientes tanto para explicar el funcionamiento interno, como el papel de la organización partidaria en el sistema político electoral. Mediante un enfoque que articula los patrones de relaciones, los resultados electorales y la ocupación de cargos partidarios, se identificaron los factores que explican el capital político que circuló en el interior del partido y garantizó su dinámica organizacional a lo largo del periodo analizado.
Organizational analysis of the Social Democracy Party of the Brazilian State of São Paulo
Keywords: Political party; Social network analysis; PSDB-SP; Organizational Dynamics; Political capital; Partido político; Análisis de redes sociales; PSDB-SP; Dinámica organizacional; Capital político